Demographic analysis: The Impact of 20 Years of Existence OF UiTM Negeri Sembilan Branch on the surrounding population / Nur Jannah Azman, Alice Shanthi Kasawi @ Krisnan and Noorlis Ahmad - Azman, Nur Jannah; Kasawi @ Krisnan, Alice Shanthi; Ahmad, Noorlis (UiTM Cawangan Negeri Sembilan, 2022)
The study on the impact of the 20-Year existence of Universiti Teknologi MARA (UiTM) Negeri Sembilan Branch, was conducted in collaboration with the Institute of Quality and Knowledge Development (InQKA) Universiti Teknologi MARA and UiTM Negeri Sembilan Branch to assess the extent to which the existence of UiTM Seremban Branch has affected the development of its surroundings and improved the socio-economic status of the population surrounding it. UiTM does not have enough and complete information on the branch campuses in formulating campus development strategies. To achieve excellence, one of the key determinants is proper planning and initiatives in strategizing. Thus, the resulting information from this study will assist UiTM’s top management in planning facilities and programs for branch campuses and show the impact of the establishment of UiTM in the socio-economic and environmental sectors. The result and data for the study was based on the analysis of the demographic information gathered from questionnaires administered on the population living around the three (3) campuses; Kuala Pilah, Seremban, and Rembau which together form UiTM Negeri Sembilan Branch. A random stratified sampling method was used to select respondents for the study. Data regarding respondents’ background and their socio-economic standing were collected from the population using questionnaire. By analyzing the data, it gave more detailed and in-depth information regarding the description and well-being of residents living around the campus. The results of the study can be used for future reference and other follow-up studies in the same discipline. This analysis is found to be very important because it gives an overview and relevance on decisions made regarding finances by the institution that encourages growth. This analysis is also important to see the relationship in terms of the three forms of economic impact namely primary, secondary, and tertiary.